Wear performances and mechanisms of ultrahard polycrystalline diamond composite material grinded against granite. (January 2016) - Yan, Gang; Yue, Wen; Meng, Dezhong; Lin, Fang; Wu, Zongyi; Wang, Chengbiao
Abstract: The wear characteristics of a novel ultrahard polycrystalline diamond (UHPCD) were verified comparing with polycrystalline diamond (PCD) through a lathe used here by grinding against granite. The wear ratios of UHPCD and PCD against granite in grinding were calculated according to the sample weight loss. The hardness and the wear morphologies of UHPCD and PCD were characterized by a micro hardness tester, a confocal laser scanning microscope (CLSM) and a scanning electron microscope (SEM). Additionally, both UHPCD and PCD were used in the manufacture of the core drilling bits. The field application tests of the bits were carried out. The results showed that the wear resistances of UHPCD under different rotate speeds are about two times than that of PCD. A cambered face which was fitted to the granite column surface formed at the end face of PCD after the wear process. Differently, a convex structure with the cutting edge of CVD diamond formed at the end face of UHPCD. The hardness of the core of UHPCD (105–115 GPa) which is higher than that of PCD (53–57 GPa) led to the different wear topographies. Higher hardness with a strong support contributes to a superior wear resistance performance. The results of field application tests reveal that the lifespan of UHPCD bits (up to 132.33 m) is superior to that of PCD bits (up to 83.76 m). These findings provide a basis for further geological application of UHPCD. Highlights: The wear performances of UHPCD in grinding against granite were evaluated. The wear resistances of UHPCD are about two times than that of PCD. A convex structure with the cutting edge of CVD diamond formed at the UHPCD fringe. Higher hardness with a strong support contributes to the superior wear resistance. The lifespan of drilling bit inserted with UHPCD is superior to that of PCD bit.